Students’ Acceptance of Teaching Interaction through the Diversity of Media in M-Learning - Amiruddin, Mohd Hasril; Sumarwati, Sri; Ismail, Mohd Erfy; Ismail, Irwan Mahazir; Rahamat, Rashidah; Marian, Mohd Fairuz; Md Amir, Nur Faizah (Online Journal for TVET Practitioners, 2021)
The technological and telecommunication development of this decade has had a profound impact, especially on the education system. In relation to this development, mobile technology in learning or M-learning is a new concept in the learning process. Examples of portable technology include PDAs (Personal Digital Assistants), Smartphones, iPads, Tablets, and more. Thus, the availability of these advanced technologies promotes an environment of m-learning among students as it is easy to carry, lightweight, and not burdensome. Through the applications of Google, Facebook, YouTube, Edmodo, Twitter, WhatsApp, and Instagram, information is available anytime and anywhere and to anyone. The objectives of this study were to identify the level of students’ knowledge of m-learning, identify students’ perceptions of m-learning, identify the applicability of students' application to m-learning and identify the relationship between students' level of knowledge and applications usage of m-learning. This questionnaire was used in the data generation, which was analyzed descriptively by using statistical Package for the Social Version 20 (SPSS Statistic 20). The respondents of this study were 204 students in the first year of Faculty Technical and Vocational Education. The finding of the study showed that the use of m-learning in the teaching and learning process has a positive impact which had a min value of 4.00 and above. Besides, this study showed that the use of m-learning is highly recommended as it provides a more engaging learning experience for students. Researchers have suggested that its use of m-learning includes urban and rural students in line with the government's goal of developing an innovative and competitive convergence-based generation.